KAYAPÓ KUKRÃDJÀ: CULTURAL MANIFESTATIONS OF INDIGENOUS PEOPLES - Ferreira Freitas, Sara (Revista Gênero e Interdisciplinaridade, 2023)
The present work aims to gather data and characteristics regarding the Kayapó indigenous peoples, proposing to observe the mythical, the symbolic, the meaning present in the culture, customs and politics of the Mebengokrê. Based on this assumption, we sought to understand the relationship with the conservation of indigenous territories, their cultural manifestations, rituals, cuisine and the artistic image as a means of expression, as well as body painting and indigenous artifacts that permeate their social life. Belonging to the Jê linguistic family, they are consolidated into 19 (nineteen) communities, occupying a territory of 11 (eleven) million hectares between the states of Mato Grosso and Pará, in the heart of the Brazilian Amazon forest